Educational Choice, Endogenous Inequality and Economic Development - Rainer Andergassen; Franco Nardini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2004)
This paper investigates the mechanics through which wealth may, in the long run, trickle down from the rich to the poor. In the presence of indivisibilities in investment of human capital and impossibility of borrowing money, investment in education is financed through an intergenerational transfer. In an OLG model where aggregate production requires capital and both skilled and unskilled labour, it is shown that the long run equilibrium outcome depends on the values of few key parameters. A complete characterisation of the steady state is provided. Under some configurations of the parameter values a unique invariant equilibrium exists where inequality vanishes asymptotically. Under others, multiple equilibria exist and the equilibrium outcome crucially depends on the initial conditions of the system. These equilibria are characterised by an negative relationship between inequality and economic development.
Keywords: 330; Bildungsverhalten; Einkommensverteilung; Vermögensverteilung; Intergenerationale Übertragung; Overlapping Generations; Qualifikation; Entwicklung; Theorie